Inclusive and Exclusive Understanding of the Doomsday Prediction Hadith: Pemahaman Inklusif dan Ekslusif Terhadap Hadis Prediksi Hari Kiamat (Takwil: Journal of Quran and Hadith Studies, 2022)
This study aims to compare the understanding of the hadith about the signs of the Day of Judgment in order to achieve an accurate understanding of the hadith of the Prophet, this research is a literature study using an analytic descriptive approach. This research is based on several pro and contra arguments related to the understanding of end-time hadith, groups or figures who welcome it with a similar response, including: the Shia sect, which thinks that at the end of time an imam named Imam Mahdi will be born who will lead the end-time ummah against all forms of abuse that is currently happening, this is what the Shi'a followers have been waiting for. Zulkifli Ali, with his argument that there is no other way than for the Muslim community to prepare themselves to welcome the arrival of Imam Mahdi and Dajjal, and the signs expressed in various hadith narrations have occurred a lot. Muhammadiyah organization, which responds to oblique hadiths that mention the appearance of an imam at the end of time (Imam Mahdi) with the argument that such an understanding comes from Shia groups that do not come from the prophet. Fazlurrahman argued that almost all hadiths that are technical in nature cannot be accounted for their authenticity to the prophet, including hadiths that discuss signs of the doomsday. This research is very urgent, because the debate over the arguments studied is directly related to facts that lead to disruption and even negative accusations against hadith speakers (Prophet Muhammad).